RELIGIOUS VALUE IN THE SHORT STORY “PEREMPUAN YANG MENARI BERSAMA OMBAK” BY RINAL SAHPUTRA - Harfiandi; Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research examines religious values as a reflection of the character of the actor who experiences an event in the story. The aim of this research is to reveal the religious values in the short story "Perempuan yang Menari Bersama Ombak". This research method uses a qualitative approach to document study. The data collected is in the form of text fragments from the characters in the short stories. The analysis used in this research is content analysis with consideration of context using table instruments. The results of the research show that there are seven text fragments in the form of religious values in short stories involving characters